Nexus of environmental, social, and governance performance in China‐listed companies: Disclosure and green bond issuance - Wang, Shanshan; Chen, Shih‐Chih; Ali, Mohd Helmi; Tseng, Ming‐Lang (Business strategy and the environment, 2024)
This study establishes a connection between existing literature on corporate environmental, social, and governance (ESG) matters, information disclosure, and green bonds by employing the issuance of green bonds to indicate investors' acknowledgment of a company's sustainable activities. Prior research has not adequately addressed the relationship between ESG performance, disclosure, and green bond issuance. A novel dataset has been compiled by merging ESG performance and information disclosure data of Chinese‐listed companies spanning from 2016 to 2020, alongside green bond issuance information from the Wind and Hexun databases. Concurrently, China's pursuit of carbon neutrality necessitates the establishment of a green, low‐carbon, and circular economy framework. ESG has surfaced as an indispensable instrument for appraising a company's sustainability and advocating the enhancement of its information disclosure systems, thereby aiding investors in forming well‐informed judgments. This study scrutinizes the correlation between each facet of ESG performance, disclosure, and green bond issuance, from the perspective of companies listed in emerging markets. The findings corroborate that companies exhibiting commendable ESG practices are more predisposed to issuing green bonds, particularly when such practices are suitably disclosed. The identified evidence will spur the enforcement of obligatory ESG disclosure regulations, further propelling China's advancement in ecological civilization and green finance.